2016
DOI: 10.1097/md.0000000000003428
|View full text |Cite
|
Sign up to set email alerts
|

Development of the A-DIVA Scale

Abstract: Placement of a peripheral intravenous catheter is a routine procedure in clinical practice, but failure of intravenous cannulation regularly occurs. An accurate and reliable predictive scale for difficult venous access creates the possibility to use other techniques in an earlier time frame.We aimed to develop a predictive scale to identify adult patients with a difficult intravenous access prospectively: the A-DIVA scale.This prospective, observational, cross-sectional cohort study was conducted between Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 29 publications
2
68
0
1
Order By: Relevance
“…Variables related to vascular access conditions were included in all the studies, though heterogeneously assessed, which prevented the development of meta-analysis. In this group, a previous history of multiple punctures 38,40,42 or a previous use of 'rescue techniques' 42,43 resulted to be significant risk factors in some studies. In addition, the ability to locate a target vein by visualization (vein visibility) or palpation (vein palpability) after tourniquet is associated to technique success and the appearance of DPIVC.…”
Section: Vascular Access Conditionsmentioning
confidence: 96%
“…Variables related to vascular access conditions were included in all the studies, though heterogeneously assessed, which prevented the development of meta-analysis. In this group, a previous history of multiple punctures 38,40,42 or a previous use of 'rescue techniques' 42,43 resulted to be significant risk factors in some studies. In addition, the ability to locate a target vein by visualization (vein visibility) or palpation (vein palpability) after tourniquet is associated to technique success and the appearance of DPIVC.…”
Section: Vascular Access Conditionsmentioning
confidence: 96%
“…Intravenous therapy can be defined as any form of treatment in which access to a vein is necessary [1,6,8]. The procedure of peripheral intravenous cannulation is performed routinely in daily clinical practice, while the first attempt to obtain an intravenous access is not successful in every patient [2,4,5,8,9,10,11]. A recently published systematic review and meta-analyses reported a failure rate of up to 30% on the first attempt of peripheral intravenous cannulation with the conventional approach [6].…”
Section: Introductionmentioning
confidence: 99%
“…This conventional approach of peripheral intravenous cannulation involves visual inspection and palpation of the extremity to locate a vein, followed by a needle puncture and catheter insertion [8,12]. Notwithstanding, intravenous access can be difficult to obtain, especially in patients with a lack of visual or palpable apparent veins, smaller veins, and in patients with a known history of a difficult intravenous access [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations